Effects of flaxseed oil supplementation on metaphase II oocyte rates in IVF cycles with decreased ovarian reserve: a randomized controlled trial - Chu, Qi; Yu, Yue-xin; Zhang, Jing-zi; Zhang, Yi-tong; Yu, Jia-ping (Frontiers in Endocrinology, 2024)
Background This study was designed to explore the effects of flaxseed oil on the metaphase II (MII) oocyte rates in women with decreased ovarian reserve (DOR). Methods The women with DOR were divided into a study group (n = 108, flaxseed oil treatment) and a control group (n = 110, no treatment). All patients were treated with assisted reproductive technology (ART). Subsequently, the ART stimulation cycle parameters, embryo transfer (ET) results, and clinical reproductive outcomes were recorded. The influencing factors affecting the MII oocyte rate were analyzed using univariate analysis and multivariate analysis. Results Flaxseed oil reduced the recombinant human follicle-stimulating hormone (r-hFSH) dosage and stimulation time and increased the peak estradiol (E2) concentration in DOR women during ART treatment. The MII oocyte rate, fertilization rate, cleavage rate, high-quality embryo rate, and blastocyst formation rate were increased after flaxseed oil intervention. The embryo implantation rate of the study group was higher than that of the control group (p = 0.05). Additionally, the female age [odds ratio (OR): 0.609, 95% confidence interval (CI): 0.52–0.72, p < 0.01] was the hindering factor of MII oocyte rate, while anti-Müllerian hormone (AMH; OR: 100, 95% CI: 20.31–495, p < 0.01), peak E2 concentration (OR: 1.00, 95% CI: 1.00–1.00, p = 0.01), and the intake of flaxseed oil (OR: 2.51, 95% CI: 1.06–5.93, p = 0.04) were the promoting factors for MII oocyte rate. Conclusion Flaxseed oil improved ovarian response and the quality of oocytes and embryos, thereby increasing the fertilization rate and high-quality embryo rate in DOR patients. The use of flaxseed oil was positively correlated with MII oocyte rate in women with DOR. Clinical trial number https://www.chictr.org.cn/, identifier ChiCTR2300073785